Band gap opening and surface morphology of monolayer graphene induced by single ion impacts of argon monomer and dimer ions. (30th October 2021) - Pradhan, Jagnaseni; Srivastava, Sachin Kumar; Palanivelu, Magudapathy; Kothalamuthu, Saravanan; Balakrishnan, Sundaravel; Sarkar, Soumya; Mathew, Sinu; Venkatesan, Thirumalai
Abstract: Craters have been observed upon irradiation by single ion impacts of Ar monomer and Ar dimer ions with 35 keV/atom in monolayer graphene on copper at a fluence of 1 × 10 12 atoms/cm 2 . The observed craters at the ion impacts are in the underlying copper substrate, which pull down the graphene layer conformally towards them, introducing disorder into graphene. The number density of craters per atom produced by Ar-monomers is higher than that of Ar-dimer ions. In the ion impact region, disorder is high, and graphene is metallic in both Ar-monomer and dimer irradiation. In the ion impact region of dimer irradiated graphene, local density of states is higher and there is a shift in Dirac point position by +0.07 eV and a bandgap opening of 0.25 eV in the ordered region ∼15 nm away from the ion impact. Microscopic ripples in graphene are not observed in the case of monomer irradiation while they are present in the case of dimer irradiation with a reduced wavelength. Isotropic compressive strain is introduced by the ion impacts and it is larger for Ar-dimer irradiation. The combined effects of compressive strain along with breaking the equivalence between A and B sublattice of graphene is attributed to the opening of the band gap in graphene. Graphical abstract: Image 1 Highlights: Craters are produced by Ar-monomer and Ar-dimer ions in monolayer graphene/Cu. In Ar-dimer irradiation, negative vicinage effect causes reduced defect density and annealing of craters. Ion impact crater region of semimetallic graphene shows metallic nature. Ar-dimer ion causes band gap opening of 250 meV in the ordered region away from crater. It is attributed to isotropic compressive strain along with symmetry breaking of sublattices of graphene.